2022
DOI: 10.1155/2022/5600804
|View full text |Cite|
|
Sign up to set email alerts
|

Invention and Clinical Application of an Oversleeve for Measuring Limb Volume in Postoperative Breast Cancer Patients

Abstract: Background. Lymphedema is a common complication of breast cancer treatment, affecting 1/5 of breast cancer survivors, but there is no reliable way to detect subclinical lymphedema. Objective. The purpose of this study was to determine the feasibility and reliability of using an oversleeve as a postoperative limb volume measurement tool in breast cancer patients. Methods. Fifty patients were analyzed based on inclusion criteria. A body volume measurement kit was designed based on the drainage volume method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%